Composition of fatty acid methyl ester in microalgae Chlorella vulgaris : Comparison between various methods of harvesting, extraction and transesterification - Nur Hidayah, Mat Yasin; Muhammad Azril, Mohd Yusop; Nur Afiqah Ayuni, Awang Kechik; Amirin Zarif, Zahuri (Elsevier Ltd, 2023)
The aim of the study was to identify which of methods produces the highest yield of fatty acid methyl ester (FAME) from microalgae. Different methods of harvesting (centrifugation, Cen & coagulation, Co), extraction (Test Tube, TT & Soxhlet, Sox) and transesterification (direct transesterification, d-trans & extraction transesterification, ext-trans) were considered. The procedures of this research consists of microalgae cultivation, harvesting of biomass and extraction of oil to obtain the lipid. The further process of converting lipid into FAME is followed by transesterification process. The FAME compositions of Chlorella vulgaris were analyzed using Gas chromatography mass spectrometry (GC–MS). The main components were consists of palmitic, stearic and oleic acids for both transesterification methods. However, FAME extracted from d-trans contained more components (linoleic and linolenic acid) than ext-trans. Furthermore, the highest amount of FAME gained by ext-trans was produced by the method of centrifugation-test tube (Cen-TT). Although Cen-TT produced the highest amount of FAME for ext-trans, it still cannot meet the highest amount of FAME produced by d-trans. Therefore, the Cen-TT method was selected to be the best microalgae harvesting and extraction method in ext-trans meanwhile the most efficient transesterification method was d-trans.